On the mainstream and independent periodicals: Álvares de Azevedo on the 1800s lusitanian press - Santos, Natália Gonçalves de Souza (Via Atlântica, 2020)
This article discusses the reception of the Brazilian writer Álvares de Azevedo in the academic press of Coimbra. For the purpose of better understanding the possible specificities of the student periodicals, the text retrieves, initially, the general perspective endorsed by the Portuguese press regarding the nascent Brazilian literature and some examples of the approach addressed to the author in the mainstream press, mainly, Lopes de Mendonça’s writings. It is in compliance with this route that the article discusses how the Azevedo’s poetry was interpreted by the university students.